Acculturing Of Arts In The Development Of Moderate Islam In TPQ - Moh Nurqosim; Rosichin Mansur; Dwi Fitri Wiyono; ali ashar (At-Tarbiyat, 2022)
Taman Pendidikan Al-Quran Nurul Huda Karangboyo Cepu Blora which is a religious education institution at the PAUD level tries to provide a learning system that provides insight to students to understand Islam broadly, especially in the field of cultural differences. This study aims to describe, analyze, and interpret the Strategy, Implementation of the Art Acculturation Model in the Development of Moderate Islam at TPQ Nurul Huda. This study uses a qualitative approach and descriptive method. The results of this study indicate that: The strategy of art acculturation in the development of moderate Islam that is applied is an integration strategy to maintain the original culture of the community by building daily interactions with Islamic art, thus forming a new art that is the result of a combination of the two. the implementation of art acculturation in the development of moderate Islam through extracurricular activities of hadrah, calligraphy, and Sufi dance can be a medium for cultivating dangdut, mural, and dance arts. The acculturation model of art is an addition by combining two different elements of art without eliminating one of the arts, but by creating new art which is the result of a combination of the two